TINJAUAN KRIMINOLOGI TERHADAP PERUSAKAN CAGAR BUDAYA MAKAM KERAMAT BANTILAN DI KABUPATEN SAMBAS - NIM. A1011161142, ORRY DWIN SEFTIANDI (Fakultas Hukum Universitas Tanjungpura, 2023)
Abstrac Cultural heritage is material cultural heritage, in the form of cultural heritage objects, cultural heritage buildings, cultural heritage structures, cultural heritage sites, and cultural heritage areas on land and/or in water whose existence needs to be preserved because they have important values for history, science, education, religion, and/or culture through the determination process, regulated in Law Number 11 of 2010 concerning Cultural Conservation, one of which is the Bantilan Sacred Cemetery with the Decree of the Sambas Regent Number: 859/DIKBUD/2017 in Bantilan Hamlet Mekar Jaya Village, Sajad District, Sambas Regency.At this time there has been a case of destroying the cultural heritage of the Bantilan Sacred Cemetery based on case number 67/Pid.Sus/2021/PN Sbs where the perpetrator violated article 66 with the criminal provisions of article 105 of Law Number 11 of 2010 concerning Cultural Conservation, then the perpetrator was sentenced imprisonment for 1 (one) year and fine in the amount of Rp. 500,000,000.00 (five hundred million rupiahs) provided that if the fine is not paid it will be replaced with imprisonment for 3 (three) months. Therefore, the issues raised in this study are to determine the factors causing the destruction of the cultural heritage of the Bantilan Sacred Tomb and to find out the efforts to deal with the destruction of the cultural heritage of the Bantilan Sacred Tomb based on a criminological review. The research method used by the author is an empirical research method with a sociological juridical approach and qualitative data analysis.The results showed that the destruction of the cultural heritage of the Bantilan Sacred Cemetery in Sambas Regency was caused by two factors, namely internal factors from the perpetrators such as low formal education, lack of legal knowledge and norms, including insufficient knowledge of cultural heritage and external factors such as the social environment. poor social welfare, as well as preventive protection efforts that are still not optimal from the Education and Culture Office of the Sambas Regency for the Bantilan Sacred Cemetery.Keywords : Cultural Heritage, Destruction of Bantilan Sacred grave, Criminology. Abstrak Cagar budaya adalah warisan budaya bersifat kebendaan, berupa benda cagar budaya, bangunan cagar budaya, struktur cagar budaya, situs cagar budaya, dan kawasan cagar budaya di darat dan /atau di air yang perlu dilestarikan keberadaannya karena memiliki nilai penting bagi sejarah, ilmu pengetahuan, pendidikan, agama, dan /atau kebudayaan melalui proses penetapan, di atur di dalam Undang-Undang Nomor 11 Tahun 2010 Tentang Cagar Budaya, salah satunya adalah Makam Keramat Bantilan dengan Penetapan SK Bupati Sambas Nomor: 859/ DISDIKBUD/2017 yang ada di Dusun Bantilan Desa Mekar Jaya Kecamatan Sajad Kabupaten Sambas.Pada saat ini telah terjadi kasus perusakan cagar budaya Makam Keramat Bantilan berdasarkan kasus perkara Nomor 67/Pid.Sus/2021/PN Sbs dimana pelaku melanggar pasal 66 dengan ketentuan pidana pasal 105 Undang-Undang Nomor 11 Tahun 2010 Tentang Cagar Budaya, kemudian pelaku divonis pidana penjara selama 1 (satu) tahun dan pidana denda sejumlah Rp 500.000.000.00 (lima ratus juta rupiah) dengan ketentuan apabila denda tersebut tidak dibayar diganti dengan pidana kurungan selama 3 (tiga) bulan. Maka dari itu permasalahan yang diangkat dalam penelitian ini adalah untuk mengetahui faktor penyebab terjadinya perusakan cagar budaya Makam Keramat Bantilan serta mengetahui upaya penanggulangan perusakan cagar budaya Makam Keramat Bantilan berdasarkan tinjauan kriminologi. Adapun metode penelitian yang digunakan oleh penulis dalah metode penelitian empiris dengan pendekatan yuridis sosiologis dan analisis data secara kualitatif.Hasil penelitian menunjukkan bahwa perusakan cagar budaya Makam Keramat Bantilan di Kabupaten Sambas di sebabkan dua faktor yaitu faktor internal dari pelaku seperti rendahnya pendidikan formal, pengetahuan hukum dan norma-norma yang kurang, termasuk pengetahuan tentang cagar budaya pun kurang dan faktor eksternal seperti akibat lingkungan pergaulan sosial yang tidak baik, serta upaya perlindungan preventif yang masih belum optimal dari Dinas Pendidikan Dan Kebudayaan Kabupaten Sambas terhadap Makam Keramat Bantilan.Kata Kunci : Cagar Budaya, Perusakan Makam Keramat Bantilan, Kriminologi.